A Disproportionately Unequal Playing Field: Challenges To and Prospect For Campaign Finance Law and Policy in The Philippines - Patricia Blardony Miranda (Association for Elections and Democracy (Perludem), 2021)
In the Philippines, the influence of money poses a challenge to political participation and representation of socially excluded, lesser-known, and historically underfunded candidates. Marginalized people and sectoral groups have to cope with discrimination alongside hurdling additional barriers of limited access to economic resources and rising campaign costs. Using Carol Bacchi’s “what is the problem represented to be?” (WPR) approach, this paper primarily interrogates how equal access to opportunities for public service is defined and represented in Philippine campaign finance law and policy. The approach also offers a conceptual framework that helps surface what remains ‘unproblematized’ by existing policy discussions and narratives. This paper contends that challenges to electoral integrity, accountability, and transparency in campaign finance are not solely due to ineffective implementation and enforcement. The WPR approach enables us to reflect on how existing policy interventions or responses to what the law identifies as problematic can also entrench elite power and replicate uneven power dynamics evident in Philippine society. Thus, for campaign finance laws to promote, rather than block, political participation and representation, additional attention must be given to the assumptions, policy gaps, and silences that give rise to anti-competitive, corrupt, and disempowering practices and norms. The resulting analysis may prove useful for outlining avenues for future law reform and policy advocacy efforts, but invite the imagining of alternative and inclusive proposals to ensure that the ability to run for public office rests on merit and ability, rather than access to financial influence and resources.